Understanding the barrier and mechanical behavior of different nanofillers in chitosan films for food packaging - Pires, João (2021)
This research was funded by national funding by FCT, Foundation for Science and Technology, through the individual research grant (SFRH/BD/144346/2019) of J.P. This study was also supported by the Associate Laboratory for Green Chemistry-LAQV, which is financed by national funds from FCT/MCTES (UIDB/50006/2020 and UIDP/50006/2020) and by the Mechanical Engineering and Resource Sustainability Center-MEtRICs, which is financed by national funds from FCT/MCTES (UIDB/04077/2020 and UIDP/04077/2020).